On the reproductive strategies post-colony foundation: Major termite pest species with distinct ecological habits differ in their oviposition dynamics - Da Silva, Iago Bueno [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Cambridge University Press (CUP), 2023)
Termite colony foundation precedes the incipient stage, when the first oviposition cycle takes place, followed by months of reproductive inactivity. The royal couple is supposed to cease oviposition during this period, investing energy to care for the first brood. When a suitable number of alloparents differentiate, egg-laying resumes. Here we followed oviposition dynamics, embryo development and queen/king body changes in laboratory colonies of the major pest species Coptotermes gestroi (Rhinotermitidae) and Cryptotermes brevis (Kalotermitidae) during 9 months. We show that they differ in these oviposition dynamics, as C. gestroi queens displayed an uninterrupted oviposition whereas C. brevis laid a cohort of eggs and ceased oviposition during a 3-month period (lag phase). C. gestroi oviposition dynamic was remarkable and suggests that occurrence of progeny was not a limiting factor, thus queens and kings were able to concomitantly invest energy in reproduction and parental care. These findings contrast those reported for rhinotermitids from temperate areas, and we discuss the likely reasons for such a condition, including endogenous rhythms, avoidance of a high mortality rate of the first progeny and adaptation to the weather conditions of the Neotropical region. Oviposition dynamic in C. brevis resembled those of several termite species, in which the royal couple cease reproduction to care for the first brood. Rearing conditions did not influence oviposition dynamics (egg-laying cycle followed by a lag phase), thus our results on the oviposition of C. gestroi and C. brevis correspond to different reproductive strategies post-foundation adopted by these pest species.
Keywords: colony foundation; egg-laying; invasive species; Kalotermitidae; Rhinotermitidae; social insects